Does Genetic Variation in PNPLA3, TM6SF2 and HSD17B13 have a Role in the Development or Prognosis of Hepatocellular Carcinoma in Turkish Patients with Hepatitis B? - EREN, FATİH (My University, 2024)
Background & Aims: Progression to hepatocellular carcinoma (HCC) is restricted by viral suppression in chronic hepatitis B (CHB); however, some patients still progress despite antiviral therapy. Presence of single nucleotide polymorphisms (SNPs) such as PNPLA3 rs738409 and TM6SF2 rs58542926 are associated with the development and progression of steatotic liver disease to HCC, whereas a splice variant in HSD17B13 rs72613567:TA has been shown to be protective. We investigated the role of these SNPs in the development or prognosis of HCC in pure CHB etiology, in the absence of hepatic steatosis, remains unknown.Materials: We analysed PNPLA3 rs738409, TM6SF2 rs58542926, and HSD17B13 rs72613567 SNPs in a prospectively recruited cohort (n=323) consisting of healthy controls, CHB and CHB-HCC patients without hepatic steatosis. SNPs were determined by PCR analysis and associations for the alleles and genotypes were investigated using adjusted-logistic regression analyses. The overall survival (OS) data were collected from CHB-HCC patients for survival analysis.Results: The genotype and allelic distribution of PNPLA3 rs738409, TM6SF2 rs58542926, and HSD17B13 rs72613567 were similar between healthy controls, CHB, and CHB-HCC groups. No genotype, allele or haplotype analysis was found to be associated with increased risk for CHB-HCC. Survival analysis revealed no genotype or allele to be associated with OS in patients with CHB-HCC.Conclusions: We could not demonstrate any association of PNPLA3 rs738409, TM6SF2 rs58542926, and HSD17B13 rs72613567 with the development or prognosis of CHB-HCC, supporting the initial hypothesis that they should be considered specific hotspots for liver diseases characterized with hepatic steatosis.
Keywords: Tıp; Sağlık Bilimleri; Temel Bilimler; Medicine; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Klinik Tıp; Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); CLINICAL MEDICINE; NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; patatin; like phospholipase-3; PNPLA3; transmembrane 6 superfamily member 2; TM6SF2; 17 beta-hydoxysteroid dehydrogenase B13; HSD17B13; hepatitis B; hepatocellular carcinoma; genetic risk score